Insights into the challenges and facilitators to physical activity among brooklyn teens enroled in a weight management programme - Viola R. Browne; Denise M. Bruno; Sarita Dhuper; Aimee Afable (Wiley, 2022)
Abstract Purpose A qualitative study was carried out to explore obese adolescents' understanding of physical activity, perceptions of the ideal body type and to identify facilitators of and barriers to physical activity. Methods Twenty‐two adolescents 12-18 years of age and 14 of their parents were recruited from an obesity intervention programme in Brooklyn, New York, from June to November 2017. Data were collected using focus groups and individual semi‐structured interviews, followed by interpretative phenomenological analysis of the transcripts. Results The adolescents wanted to 'lose some weight', but not to be 'thin' or 'look hungry'. Most females desired a 'slim‐thick' figure, which was 'a flat stomach with big thighs, and curvy'. Fun and support from parents, peers and programme staff facilitated achieving their physical activity goals. Barriers included low self‐efficacy, inactive families, fear of neighbourhood gangs and crime and perceptions that the parks were small and overcrowded, with limited physical activity options for adolescents. Conclusion These findings highlight the need to consider local norms concerning body image when designing obesity interventions. To effectively reduce childhood obesity in New York City, policy should prioritize the promotion of public safety, improvement of neighbourhood parks and increase options for physical activity. Patient or Public Contribution The voices and narratives of patients and their families informed this study.